The invention of the monolingualism and national language - Henrique Monteagudo (Gragoatá, 2012)
Societal monolingualism, far from being a spontaneous phenomenon, is usually the outcome of glotopolitical interventions aimed at the uniformization of previously multilingual populations. This outcome is achieved and artificially sustained by deliberate institutional and governmental policies. This contribution explains how these historical processes are connected to the emergence of Nation-States and States-Nation established in Europe form the 18th century on. At the same time, the ideology of the ‘national language’ was elaborated and disseminated, so the cultural, socio-political and practical conditions for the creation of monoligual spaces were achieved.